PENGARUH AUDIT DELAY, AUDIT TENURE, DAN KOMITE AUDIT TERHADAP KUALITAS AUDIT - Nursyamsyiyah, Vivi; Zakaria, Adam; Nasution, Hafifah (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research was conducted with the aim of finding out the influence of audit delay, audit tenure, and audit committee on audit quality. This research uses companies in the property and real estate sector listed on the Indonesia Stock Exchange during the 2020-2022 period as the population. The research sample was selected using the purposive sampling method and produced 168 observation data. Data were analyzed using logistic regression analysis techniques and processed with SPSS 26. The research results show that audit delay has a negative effect on audit quality, while audit tenure and audit committee have no effect on audit quality